1035325 Gambaran Pendidikan dan Pengetahuan yang Mempengaruhi Imunisasi Campak Booster Pada BATITA - Tirta Anggraini (STIKes Budi Mulia Sriwijaya, 2019)
ABSTRACT Basic immunization is the initial immunization to achieve immune levels above the protective threshold. This immunization is given to infants between the ages of 0-12 months, consisting of BCG, DPT, polio, hepatitis B, measles immunization. Repeat immunization (booster) is the provision of immunity after basic immunization or in children aged 24-36 months receiving hepatitis B immunization , then as soon as possible given hepatitis immunization with a schedule of 3 times. According to the World Health Organization (WHO), the number of births in 2009 was recorded at 4,174,000, followed by a report on the number of living babies for 4,071,000. And the coverage of basic immunization for children increased from 5% to close to 80% throughout Indonesia. According to data in Indonesia, the Immunization Target is as much as 90% to get immunized and that means there are still 10% of babies in Indonesia who have not received complete basic immunization every year, so this can have an impact on babies who are not immunized, namely very vulnerable to viruses that will be attacks the baby's body and can cause infant mortality, Immunization in 2015 reached 90%, so that 4.5 million babies in Indonesia have received complete basic immunization. Bukit Sangkal Palembang in 2017. Sampling was done by accidental sampling. With a sample size of 30 respondents, the data were analyzed using univariate analysis. The results of this study indicate that mothers who have good knowledge (75.0%) than mothers who have poor knowledge (25.0%). Mothers with high education (63.3%) compared to mothers with low education are educated (36.7%) Keywords: Education and knowledge that affect Booster Measles Immunization